2009
DOI: 10.1366/000370209789553183
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Surface-Enhanced Raman Spectroscopy Based Analysis of MicroRNA Mixtures

Abstract: We have developed a rapid, sensitive, and quantitative method for identification of microRNA (miRNA) sequences in multicomponent mixtures using surface-enhanced Raman spectroscopy (SERS). The method uses Ag nanorod array substrates prepared by oblique angle vapor deposition as the SERS platform. We show that Ag nanorod-based SERS spectra are uniquely characteristic for each miRNA sequence studied, and that the spectral reproducibility is sufficient for quantitative analysis of miRNA profiles in multicomponent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 45 publications
(53 reference statements)
1
54
0
2
Order By: Relevance
“…However, we have previously demonstrated that silver nanorod (AgNR) substrates demonstrate excellent reproducibility for SERS measurements (∼10% relative standard deviation) 8,9 and have been successfully employed for quantitative DNA detection. 10,11 Second, the target−probe duplex is composed of the same four nucleotide components as the probe sequence, and therefore, the SERS signals before and after hybridization are very similar. One method that can be used to discriminate among highly similar SERS spectra is to use multivariate statistical approaches such as principal component analysis (PCA) or partial least-squares (PLS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have previously demonstrated that silver nanorod (AgNR) substrates demonstrate excellent reproducibility for SERS measurements (∼10% relative standard deviation) 8,9 and have been successfully employed for quantitative DNA detection. 10,11 Second, the target−probe duplex is composed of the same four nucleotide components as the probe sequence, and therefore, the SERS signals before and after hybridization are very similar. One method that can be used to discriminate among highly similar SERS spectra is to use multivariate statistical approaches such as principal component analysis (PCA) or partial least-squares (PLS).…”
mentioning
confidence: 99%
“…One method that can be used to discriminate among highly similar SERS spectra is to use multivariate statistical approaches such as principal component analysis (PCA) or partial least-squares (PLS). 10,11 In the current report, we propose the use of SERS in conjunction with a straightforward least-squares (LS) regression approach for quantitative determination of the composition of heterogeneous DNA probe sequences immobilized on the surface AgNR substrates. The LS method was previously adopted by Prado et al 12 to decipher the physical ratios of pure homogeneous nucleotide sequences within a mixture of sequences using SERS.…”
mentioning
confidence: 99%
“…1) PLS2: PLS2 iteratively deflates on to obtain residual matrix and the corresponding projection direction by solving the following formulization: (6) where is calculated from a deflation process described in Algorithm 1, in which, is the first eigenvector of matrix corresponding to the largest eigenvalue. The projecting direction is to project residual matrix , and the projecting directions of original data set can be calculated as [26] or [18].…”
Section: B Plsr Methodsmentioning
confidence: 99%
“…Quantitative analysis of spectrum is also called spectroscopic calibration, which is mainly to determine the chemical or physical properties of an analyte (e.g., concentrations of pure components in the compound) from its measured spectrum. The state-of-the-art analysis method is partial least square regression (PLSR) [3], [6], [17], [24], [31], which is developed from partial least squares (PLS) method. A recent overview of PLS can be found in [22].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we fabricate SERS substrate both under normal operating pressure at 0.5 Pa (sample I and II) and higher pressure at 1 Pa (sample III and IV). To date, the most effective SERS substrate based on silver nanorod structure was successfully fabricated by an e-beam evaporation system using an oblique-angle deposition technique [57][58][59][60]. Surprisingly, there is no report on fabrication SERS substrate using such a technique by a sputtering system.…”
Section: Sers Substrate Preparationmentioning
confidence: 99%